Hollow Mesoporous Organic Polymeric Nanospheres (HMOPNs)‐Supported Carbene Rovis Catalyst: Mesopore and Morphology‐Dependent Catalytic Performances in Asymmetric Organocascade. Issue 20 (13th September 2018) - Teng, Fei; Xie, Guangxing; Zhang, Li; Ma, Xuebing
Abstract: In view of the vital functions of mesopore and hydrophobicity of organic polymer in the mass transfer of reactants and enantioselectivity in heterogeneous asymmetric organocatalysis, a novel type of well‐shaped hollow mesoporous organic polymeric nanospheres (HMOPNs)‐supported triazolium carbene Rovis catalyst was developed for the first time by the copolymerization of styrene and vinylated triazoline on the surface of polystyrene nanosphere (PS), etching of PS template by THF and then trityl cation‐mediated oxidation. The as‐fabricated well‐shaped HMOPNs with mesoporous shell and thin shell thickness was proven to be highly active in asymmetric Michael/Stetter cascade with the higher yields and enantioselectivities than mesopore‐deficient polystyrene‐supported triazolium carbene Rovis catalyst (PS‐7), and achieve the same enantioselectivities as corresponding homogeneous triazolium carbene Rovis catalyst. The as‐fabricated mesopores in the shell of HMOPNs played an important role in enantioselectivity on the basis of the calculated transition state of Breslow intermediate. Moreover, the HMOPNs‐supported Rovis catalyst displayed good reusability and mechanical stability in batch repeated experiments. Abstract : Row, row, rovis your boat : A novel type of well‐shaped hollow mesoporous organic polymeric nanospheres (HMOPNs)‐supported triazolium carbene Rovis catalyst was developed for the first time. The unique advantages of HMOPNs with mesoporous shell and thin shell thickness enhanced mass transfer and enantioselectivity in heterogeneous asymmetric Michael/Stetter organocascade.